Analysis of Band-Pass Filter Characteristics in a Ferrite Device with Carbon Nanotube Electrodes - Umegaki, Toshihito; Ogawa, Matsuto; Miyoshi, Tanroku (Applied Computational Electromagnetics Society Journal (ACES), 2022)
We have studied magnetostatic waves excited and received by carbon nanotubes in the high-frequency band-pass filter on yttrium iron garnet (YIG). First, we have analyzed dispersion curves of magnetostatic waves in YIG based upon the magnetostatic approximation method. We have studied the characteristics of the band-pass filter where the high-frequency current flowing on single-wall CNTs may excite and receive directly magnetostatic waves in the ferrite film beneath them. Next, we have studied the device where the current is flowing on bundle CNTs. It is found that band-pass filter characteristics, such as the insertion loss (IL), the center frequency (f0), and bandwidth (BW) are significantly controlled by both the chirality of the CNTs and the numbers of CNTs in the bundle CNTs. On these results, we have proposed a novel ferrite device which may work to discriminate the chirality of CNTs and the numbers of CNTs in a bundle CNT. In this device, the chirality or the number of CNTs in a bundle CNT may be measured by means of the band-pass characteristics via the wavelength of the operating magnetostatic waves.